Pengembangan Lembar Kerja Peserta Didik (LKPD) IPA Berbasis Model Problem Based Learning (PBL) Di Kelas IV Sekolah Dasar - Surya Widia Lestari; Muhammad Subhan; Deded Pratama (Jurnal Dharma PGSD, 2021)
ABSTRACT: This development research aims to: 1) produce products in the form of LKPD Science teaching materials based on Problem Based Learning (PBL) Models. 2) find out how appropriate IPA LKPD Based Problem Based Learning (PBL) model is used to help and facilitate students in understanding the concept of the material presented. 3) find out how much the increase in student learning outcomes using IPA LKPD Based on Problem Based Learning (PBL) Models. This research is a development research with 4-D model. Research instruments include: validation sheets, practical observation sheets and tests of effectiveness. The data analysis technique uses validation analysis, practicality analysis and effectiveness analysis. The results of the study: 1) LKPD IPA teaching materials based on the Problem Based Learning (PBL) model were feasible and valid with a percentage of 82.06% with a very valid category. 2) the results of the trial of the IPA LKPD product based on the Problem Based Learning (PBL) model showed a percentage of 96% categorized as very practical. 3) student learning test results show a percentage of 92.85% with a very effective category.